Microwell Plate-Based Dynamic Light Scattering as a High-Throughput Characterization Tool in Biopharmaceutical Development - Katharina Dauer; Stefania Pfeiffer-Marek; Walter Kamm; Karl G. Wagner (MDPI AG, 2021)
High-throughput light scattering instruments are widely used in screening of biopharmaceutical formulations and can be easily incorporated into processes by utilizing multi-well plate formats. High-throughput plate readers are helpful tools to assess the aggregation tendency and colloidal stability of biological drug candidates based on the diffusion self-interaction parameter (kD). However, plate readers evoke issues about the precision and variability of determined data. In this article, we report about the statistical evaluation of intra- and inter-plate variability (384-well plates) for the kD analysis of protein and peptide solutions. ANOVA revealed no significant differences between the runs. In conclusion, the reliability and precision of kD was dependent on the plate position of the sample replicates and kD value. Positive kD values (57.0 mL/g, coefficients of variation (CV) 8.9%) showed a lower variability compared to negative kD values (−14.8 mL/g, CV 13.4%). The variability of kD was not reduced using more data points (120 vs. 30). A kD analysis exclusively based on center wells showed a lower CV (<2%) compared to edge wells (5-12%) or a combination of edge and center wells (2-5%). We present plate designs for kD analysis within the early formulation development, screening up to 20 formulations consuming less than 50 mg of active pharmaceutical ingredient (API).